2017
DOI: 10.1128/msphere.00410-17
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Antibiotics with Innate Host Defense Factors against Salmonella enterica Serotype Newport

Abstract: It is becoming increasingly understood that the current paradigms of in vitro antimicrobial susceptibility testing may have significant shortcomings in predicting activity in vivo. This study evaluated the activity of several antibiotics alone and in combination against clinical isolates of Salmonella enterica serotype Newport (meningitis case) utilizing both conventional and physiological media. In addition, the interactions of these antibiotics with components of the innate immune system were evaluated. Azit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…Synergistic enhancement of antimicrobial activities has been described (McCafferty et al 1999;Acar 2000) and includes mixtures of peptides with conventional antibiotics (Chou et al 2016;Bolosov et al 2017;Kim et al 2017;Payne et al 2017;Rank et al 2017;Sakoulas et al 2017) or different peptides such as dermaseptins, bacteriocins (Mor et al 1994;McCafferty et al 1999), magainin 2 and PGLa (Vaz Gomes et al 1993), or magainin and the cyclic β-sheet tachyplesin I sequence (Kobayashi et al 2001). Here we will shortly summarize findings made with magainin 2 and PGLa which have recently been reviewed in more detail (Marquette and Bechinger 2018).…”
Section: Synergistic Enhancement Of the Activities Of Antimicrobial Pmentioning
confidence: 95%
“…Synergistic enhancement of antimicrobial activities has been described (McCafferty et al 1999;Acar 2000) and includes mixtures of peptides with conventional antibiotics (Chou et al 2016;Bolosov et al 2017;Kim et al 2017;Payne et al 2017;Rank et al 2017;Sakoulas et al 2017) or different peptides such as dermaseptins, bacteriocins (Mor et al 1994;McCafferty et al 1999), magainin 2 and PGLa (Vaz Gomes et al 1993), or magainin and the cyclic β-sheet tachyplesin I sequence (Kobayashi et al 2001). Here we will shortly summarize findings made with magainin 2 and PGLa which have recently been reviewed in more detail (Marquette and Bechinger 2018).…”
Section: Synergistic Enhancement Of the Activities Of Antimicrobial Pmentioning
confidence: 95%
“…All of these components modulate various pathways and are mainly causative for the altered in vivo efficiency of antibiotics. [69,[71][72][73][74] Efforts were made to mimic in vivo conditions during in vitro AST to account for this contextual antibiotic susceptibility.Astraightforward and very effective approach is the substitution of common rich laboratory medium with minimal medium. [75,76] Ar ecent study by Ersoy et al revealed that the antibiotic susceptibility of various clinical isolates strongly depends on the medium used for in vitro cultivation.…”
Section: Screening Platformsmentioning
confidence: 99%
“…The lack of predictive value is partly attributed to the fact that the growth media in which the susceptibility tests are conducted, do not sufficiently represent the in vivo environment. Several factors, such as nutrient availability, oxygen level, pH and presence of innate immune components, have been identified to affect antibiotic susceptibility in both Gram-positive and –negative species 2225 . Here we show that the presence of the antimicrobial peptide LL-37 of the innate immune response antagonizes the activity of vancomycin against S. aureus in vitro .…”
Section: Resultsmentioning
confidence: 99%